Prediction of Active Sites of Bitter Taste Receptors through X-ray Crystal Structure of COX-2 Enzyme - Karaman, Rafik; Mecca, Gennaro; Jumaa, Salma (Pharmaceutical Research - Recent Advances and Trends Vol. 1, 2024)
Conventional taste masking methods including the use of sweeteners, amino acids and flavoring agents are often inadequate in masking the taste of highly bitter substances such as NSAIDs, i.e. ibuprofen, diclofenac sodium, mefenamic acid and etc., especially when these drugs are administered via the orally as syrups or solutions. The X-ray crystal structure of the enzyme COX-2 and the chemical structures of widely used non-steroidal anti-inflammatory drugs (NSAIDs) that bind to COX enzymes and activate the bitter taste receptor TAS2R14 are used in this commentary to discuss a novel approach to be used in the design of active sites of bitter taste receptors, especially TAS2R14. In order to better understand the nature of the interactions between bitter tastants and the chemical groups within the active site of the TAS2R14 receptor, the suggested approach entails docking calculations of the NSAIDs (ligands) to the active site of COX-2.